Trans people, well-being, and labor market outcomes - Nick Drydakis (IZA World of Labor, 2017)
Acceptance of one's gender identity and congruence between one's gender identity and outward appearance are associated with less adverse mental health symptoms, and greater life and job satisfaction. However, trans people are subject to human rights violations, hate crimes, and experience higher unemployment and poverty than the general population. Trans people often feel that they are citizens who are not allowed to be themselves and practice their authentic identity. Many biased treatments of trans people could be attenuated if legal protections and inclusive workplace practices were in place.
Keywords: 330; trans; transitioning; mental health; job satisfaction; discrimination